Characterizations of Euclidean Spheres in Terms of the Tangential Part of the Position Vector Field - Mona Bin-Asfour; Kholoud Saad Albalawi; Mohammed Guediri (International Journal of Mathematics and Mathematical Sciences)
In this study, we utilize the support function θ and the tangential component ψT of the position vector field ψ to investigate certain properties of spheres on a compact hypersurface in Euclidean space Rn+1. The first characterization expands upon existing results in the literature by removing constraints on the tangential component ψT and employing alternative proof techniques. In the second characterization, we specifically employ the support function θ.